2021
DOI: 10.3390/jcm11010199
|View full text |Cite
|
Sign up to set email alerts
|

Poor Long-Term Renal Allograft Survival in Patients with Chronic Antibody-Mediated Rejection, Irrespective of Treatment—A Single Center Retrospective Study

Abstract: The Banff 2017 report permits the diagnosis of pure chronic antibody-mediated rejection (cAMR) in absence of microcirculation inflammation. We retrospectively investigated renal allograft function and long-term outcomes of 67 patients with cAMR, and compared patients who received antihumoral therapy (cAMR-AHT, n = 21) with patients without treatment (cAMRwo, n = 46). At baseline, the cAMR-AHT group had more concomitant T-cell-mediated rejection (9/46 (19.2%) vs. 10/21 (47.6%); p = 0.04), a higher g-lesion scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In addition, the AHT regimen with enhanced immunosuppression led to a higher number of over immunosuppression and conferred a substantial risk of drug-toxicities, which was closely associated with the deterioration of the tubulointerstitial fibrosis and inferior late graft survival ( 67 ). Several studies highlight the importance of progressive fibrosis as a key pathway to graft failure and a target for intervention independent of the role of AMR in late graft failure ( 11 , 62 ). Therefore, the ideal therapeutic guidelines for TG remain to be determined, and the choice of appropriate medication dosage, paired with careful patient monitoring and adjustment of baseline immunosuppression, needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the AHT regimen with enhanced immunosuppression led to a higher number of over immunosuppression and conferred a substantial risk of drug-toxicities, which was closely associated with the deterioration of the tubulointerstitial fibrosis and inferior late graft survival ( 67 ). Several studies highlight the importance of progressive fibrosis as a key pathway to graft failure and a target for intervention independent of the role of AMR in late graft failure ( 11 , 62 ). Therefore, the ideal therapeutic guidelines for TG remain to be determined, and the choice of appropriate medication dosage, paired with careful patient monitoring and adjustment of baseline immunosuppression, needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Later, a C4d-negative cAAMR was recognized in Banff 2013 report ( 10 ), and peritubular capillary C4d deposits could be replaced by at least moderate microcirculation inflammation (MVI). However, it is not uncommon for the three diagnostic features of cAAMR to appear as an incomplete combination, and different features of disease activity in the biopsy may be more reflective of the variable phenotypes of AMR ( 11 ). As a consequence, the Banff 2017 report ( 12 ) permits the diagnosis of chronic AMR (cAMR) with TG and current or recent DSA in absence of the capillary C4d deposits or at least moderate MVI.…”
Section: Introductionmentioning
confidence: 99%
“…Another multicentre study that included 91 patients with caABMR observed death-censored graft survival of 36.4% at 5 years [28]. Other studies in patients with caABMR have observed a graft survival of 50% at 1-2 years and 32% at five years after diagnosis [5,27,29]. DSA+ KTR have been proven to have a higher risk of graft loss [30,31]; however, all our patients in the caABMR group had DSA.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, there is no consensus regarding the management of renal transplant recipients without allograft dysfunction with circulating de novo DSAs [ 16 ]. The impact of de novo anti-HLA DSAs on the development of ABMR is under investigation, as not all DSA-positive patients develop ABMR [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%